Analisis Penggunaan Flipgrid Sebagai Media Pembelajaran Berbasis Video dalam Meningkatkan Kemampuan Berbicara Peserta Didik Sekolah Dasar - Febriyanti, Mita Tri; Suhaili, Nora Wyrentia; Supriyadi, Supriyadi; Hermawan, Jody Setya (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is to analyze how the use of Flipgrid as a video-based learning medium can improve the speaking skills of elementary school students. The method used in this study is qualitative research, utilizing literature review to analyze existing research findings. The steps will involve gathering prior research related to Flipgrid and video-based learning, then analyzing data from available reports or documents, and finally drawing conclusions based on the findings from the literature review. The results indicate that the use of Flipgrid as a video-based learning medium has a positive impact on the speaking skills of elementary school students. In addition to enhancing technical speaking abilities such as fluency and articulation, Flipgrid also helps improve motivation, self-confidence, and strengthens interaction in the learning process.